สมบัติและลักษณะเฉพาะของเส้นใยไหมที่ผลิตในประเทศไทย - ปิยวรรณ ปุยเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This research has an aim to study properties and characterization of silk fiber produced in Thailand. The selected three silk fibers used in this research are two species of Thai silk fibers namely the yellow silk type consisting of one species each Nang Noi Srisaket 1, and Sam Rong 1 species as the first type. The second type is three species of mixed hybrid Thai silk fiber of Dok Bua species and Chul 4 species having yellow color, and Chul 6 of white color. The third type is the mixed hybrid foreign silk fiber comprising the white silk fiber of Chul 1 species. On characterization, these three silk fibers possess similar properties such as, chemical fundamental composition, triangular cross-sectional fiber, fire ignition, fire extinction and ash appearance, and fiber evenness. The amount of crystallinity of raw silk fiber is 37-48% while the degummed silk contains 32-45% crystallinity. Melting points of raw and degummed silk fiber are 146-160°C and 140-155°C, respectively. The relative densities are between 1.0- 1.2 g cm³. Besides, the three silk fibers show high resistance to acid while being destroyed by alkali and bleaching agent. The differences among the three silk fibers can be found as follows. The raw Thai silk fiber has the highest denier of 2.2-2.9 with the greatest amount of sericin of 37% while the Leub mixed hybrid Thai silk fiber has the lowest sericin of 19-20%. In addition, it is found that the native Thai silk fiber is the strongest, contains the highest moisture content in fiber of 7-10%, and can be dyed to the deepest shade especially the native Thai species Nang Noi Srisaket 1. As conclusions, the most suitable yellow silk fiber for textile applications is the native Thai, Nang Noi Srisaket 1, and the mixed hybrid Thai silk fiber, Dok Bua. For the white silk fiber, the most suitable species is the mixed hybrid foreign species, Chul 1. Nonetheless, all silk fibers used in the present studies own suitable properties for textile applications.